Venezuelan Migration and the Border Health Crisis in Colombia and Brazil. (September 2019) - Doocy, Shannon; Page, Kathleen R.; de la Hoz, Fernando; Spiegel, Paul; Beyrer, Chris
Executive Summary: : Venezuela's economic crisis has triggered mass migration; more than 3.4 million Venezuelans have fled to other countries in the region and beyond. An assessment mission to Cúcuta, in the Colombian border state of North Santander, was undertaken from July 26 to August 1, 2018, and to Bôa Vista and Pacaraima, in the state of Roraima, Brazil, between August 24 and 28, 2018. Interviews were conducted with key informants, including health providers and organizations engaged in the humanitarian response. Secondary analysis of gray literature and data shared by key informants was also undertaken. Surveillance data demonstrate increases in infectious diseases, as well as adverse maternal and neonatal health outcomes, among Venezuelans in North Santander and Roraima. Summary of Findings for North Santander: Reportable public health surveillance events among Venezuelans increased from 182 in 2015 to 865 in the first half of 2018. In 2018, the most common reported events included gender-based and intrafamiliar violence (17 percent), malaria (15 percent), and acute malnutrition in children <5 years (9 percent). There were 14 measles cases reported between January and June 2018 (compared to none in the previous years), the majority associated with migration from Venezuela. Thirty-six cases of maternal morbidity and two cases of maternal mortality among Venezuelans were observed in the first half of 2018 (compared to three cases of maternal morbidity and no maternal deaths in 2015). Low-birth-weight Venezuelan births rose from three in 2015 to 34 in 2017. Between January 2017 and June 2018, emergency medical attention was provided to 19, 108 Venezuelans in government health facilities. Summary of Findings for Roraima: In 2018, there were 355 cases of measles in Roraima (compared to none in previous years) — all cases had the genotype lineage originating in the 2017 Venezuelan measles outbreak. Children younger than one year old (812.1/100, 000) had the highest measles incident rate in Roraima, followed by children 1–4 years old (245.7/100, 000). Malaria cases among Venezuelans increased 3.5-fold from 2015 to 2018 (1, 260 vs. 4, 402 cases). As of August 2018, 171 HIV-infected Venezuelans were receiving HIV care at the Coronel Motta Clinic in Bôa Vista, Roraima. In 2018, 1, 603 Venezuelan women gave birth at the Hospital Materno-Infantil in Bôa Vista, and by mid-2018, 10, 040 Venezuelans had received outpatient care and 666 had been hospitalized at the Hospital General Roraima. : In Colombia, primary healthcare is not available to Venezuelans, and provision of emergency care is perceived as unsustainable given current funding mechanisms. In Brazil, primary care is available to Venezuelans, but the healthcare system is under severe strain to meet the increased demand for care and is facing unprecedented shortages in medications and supplies. There is an urgent need to expand the humanitarian health response in Colombia and Brazil, both to ensure health among Venezuelans and to protect public health in border areas.